2022
DOI: 10.29333/ejgm/11545
|View full text |Cite
|
Sign up to set email alerts
|

Being An Infertile Woman in A Highly Fertile Region of Turkey: Stigmatisation and Coping Experiences

Abstract: In many societies, women's status is determined by their fertility and motherhood, and having reproductive disorders creates additional problems for them. This study investigates the stigmatisation of infertile women and how they cope in a region with the highest fertility rate in Turkey. Methods:The sample population this descriptive study comprised of infertile women who applied to the infertility clinic of a university hospital in Sanliurfa. In the pilot study conducted with 19 participants, the stigmatisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This scale evaluates an individual’s perceived and self-stigma [ 57 ]. The ISS has been widely used in studies in China and Turkey [ 22 , 26 , 27 , 28 , 31 , 33 , 34 , 55 ]. The scale contains 27 items that can be divided into four subscales: self-devaluation, social withdrawal, public stigma, and family stigma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This scale evaluates an individual’s perceived and self-stigma [ 57 ]. The ISS has been widely used in studies in China and Turkey [ 22 , 26 , 27 , 28 , 31 , 33 , 34 , 55 ]. The scale contains 27 items that can be divided into four subscales: self-devaluation, social withdrawal, public stigma, and family stigma.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the stigma of infertility is negatively associated with mental health, leading to anxiety, depression, social avoidance, and low quality of life [ 13 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Stigma is a socially constructed process wherein a group with certain characteristics is labeled with socially unfavorable attributes and, in turn, is slighted by the general public by virtue of attributes or behaviors socially deemed undesirable exhibited by that group [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these factors, studies have shown that the stigma of infertility has negative impacts on health, including psychological distress such as anxiety and depression, low quality of life, and social isolation [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Stigma refers to the socially constructed process by which a group of individuals are labeled with socially undesirable attributes.…”
Section: Introductionmentioning
confidence: 99%